The impact of hop bitter acid and polyphenol profiles on the perceived bitterness of beer - Oladokun, Olayide; Tarrega, Amparo; James, Sue; Smart, Katherine; Hort, Joanne; Cook, David (Elsevier, 2016)
Thirty-four commercial lager beers were analysed for their hop bitter acid, phenolic acid and polyphenol contents. Based on analytical data, it was evident that the beers had been produced using a range of different raw materials and hopping practices. Principal Components Analysis was used to select a sub-set of 10 beers that contained diverse concentrations of the analysed bitter compounds. These beers were appraised sensorially to determine the impacts of varying hop acid and polyphenolic profiles on perceived bitterness character. Beers high in polyphenol and hop acid contents were perceived as having ‘harsh’ and ‘progressive’ bitterness, whilst beers that had evidently been conventionally hopped were ‘sharp’ and ‘instant' in their bitterness. Beers containing light-stable hop products (tetrahydro-iso-α-acids) were perceived as ‘diminishing’, ‘rounded’ and ‘acidic’ in bitterness. The hopping strategy adopted by brewers impacts on the nature, temporal profile and intensity of bitterness perception in beer.